Crisis and populism: a comparative study of populist and non-populist candidates and rhetoric in the news media coverage of election campaigns - Salgado, Susana (2021)
This research investigates links between the Euro Crisis and populism and asks whether there are patterns of populism in different election campaigns, namely is there country-specific populist rhetoric or similar anti-elite criticisms? Through content analysis, we examine the mainstream media coverage of populist and non-populist actors in the countries that were most affected by the Euro Crisis (Greece, Ireland, Portugal, Spain) and in Poland, a country that, despite not being part of the Euro, has been experiencing a significant rise of populism recently. These are also countries underrepresented in systematic empirical political communication research and that represent different levels of success of populism. Our findings show that although mainstream news media tends to be negative towards populist candidates, there are important cross-country differences with potential impact on the electoral success and failure of populist actors.